Thrombotic Thrombocytopenic Purpura Induced by Acute Pancreatitis - Roedan, MD, Socrates G; Shah, MD, Nihar N; Spira, MD, Robert (North American Journal of Medicine and Science, 2016)
Thrombotic thrombocytopenic purpura (TTP) is a rare blood disorder characterized by clotting in small blood vessels of the body (microthrombi), resulting in a low platelet count. The disease consists of the pentad of microangiopathic hemolytic anemia, thrombocytopenic purpura, neurologic abnormalities, fever and renal disease. Many symptoms could develop with acute pancreatitis but being able to differentiate when it is associated with any hematological conditions such as TTP is crucial to initiate a proper medical treatment. We present a rare case of a thirty-eight years old African American female, who presented to the Emergency department with an abdominal pain associated with a pancreatic condition. A vital piece in medical practice is recognizing lifesaving decisions in critical conditions cases. Acute Pancreatitis (AP) is a well-described consequence of TTP but acute pancreatitis triggering TTP is still not as frequent. [N A J Med Sci. 2016;9(2):75-77. DOI: 10.7156/najms.2016.0902075]